2016
DOI: 10.1038/srep34019
|View full text |Cite
|
Sign up to set email alerts
|

Expression of immunoproteasome genes is regulated by cell-intrinsic and –extrinsic factors in human cancers

Abstract: Based on transcriptomic analyses of thousands of samples from The Cancer Genome Atlas, we report that expression of constitutive proteasome (CP) genes (PSMB5, PSMB6, PSMB7) and immunoproteasome (IP) genes (PSMB8, PSMB9, PSMB10) is increased in most cancer types. In breast cancer, expression of IP genes was determined by the abundance of tumor infiltrating lymphocytes and high expression of IP genes was associated with longer survival. In contrast, IP upregulation in acute myeloid leukemia (AML) was a cell-intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 54 publications
(65 reference statements)
6
75
0
Order By: Relevance
“…For Bortezomib, we observed significant associations for different proteasome subunits such as subunit alpha (PSMA) and beta (PSMB). These subunits have been shown to be key players across different cancers (Rouette et al, 2016;Tsvetkov et al, 2017;Li et al, 2017). We also observed significant associations for RELA (also known as Transcription Factor p65) in all of the studied cancers which aligns with its oncogenic role across different cancers (Collignon et al, 2018), and moreover, with its reported associations with Bortezomib in breast cancer (Hideshima et al, 2014), prostate cancer (Manna et al, 2013), and lung cancer (Zhao et al, 2015).…”
Section: Aitl Predictions For Tcga Patients Have Significant Associatsupporting
confidence: 76%
“…For Bortezomib, we observed significant associations for different proteasome subunits such as subunit alpha (PSMA) and beta (PSMB). These subunits have been shown to be key players across different cancers (Rouette et al, 2016;Tsvetkov et al, 2017;Li et al, 2017). We also observed significant associations for RELA (also known as Transcription Factor p65) in all of the studied cancers which aligns with its oncogenic role across different cancers (Collignon et al, 2018), and moreover, with its reported associations with Bortezomib in breast cancer (Hideshima et al, 2014), prostate cancer (Manna et al, 2013), and lung cancer (Zhao et al, 2015).…”
Section: Aitl Predictions For Tcga Patients Have Significant Associatsupporting
confidence: 76%
“…Carfilzomib 3 is the most potent compound displaying fast onset and sustained inhibition at 13 h pre‐incubation time while the ketoamides show slower onset of inhibition highest for 27 and lower for 9 and 7 . However, in THP‐1 cells the inhibitors show altered potency in inhibiting conversion of 30 , presumably as iCP expression is higher than in MV4‐11 and Jurkat cells . After short incubation times 3 is the most potent compound, while inhibition is decreased with incubation time, leading to lower inhibition after 13 h incubation time for 9 and 27 .…”
Section: Resultsmentioning
confidence: 97%
“…Carfilzomib 3 is the most potent compound tested in the acute monocytic leukemia‐derived cell line MV4‐11, whereas 27 is more potent in Jurkat cells than 3 , a cell line derived from T‐cell leukemia. Interestingly, both inhibitors show much reduced activity in THP‐1 cells, also derived from acute monocytic leukemia expressing presumably iCP correlating with more potent inhibition of β5c over β5i by 3 and 27 . Furthermore, inhibition of cellular conversion of substrate 30 correlates with altered sensitivity in these cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis using the MALDI-TOF mass spectrophotometry (MS) based on two-dimensional polyacrylamide gel electrophoresis (2-DE) of breast cancer tissues showed over-expression of these proteasomes subunit proteins, including PSMD2 and PSMA1, when compared to normal adjacent tissue, which enhanced the action of ubiquitin-proteasome pathway in breast cancer tissues [31]. Analysis of thousands of tumor samples from The Cancer Genome Atlas (TCGA) reported an increased expression of proteasomes such as PSMB6, PSMB7 [32], and PSMD2 [30] in most cancer types. Other members of the proteasomal protein of this network such as the PSMB7 was reported to be over-expressed in colorectal cancer [33], whilst PSME2 along with PSME3 were reported to be significantly enriched in several biological processes and pathways including cell adhesion, adherent junction organization, regulation of autophagy, cellular protein localization, the cell cycle, and the apoptosis pathway [34].…”
Section: Discussionmentioning
confidence: 99%